Growth and Production Response of Varieties of Mung Beans (Vigna radiata L.) to Gibberellin Concentration in the Saline Field - Rina Atika; Eva Sartini Bayu; Emmy Harso Kardhinata (Talenta Publisher, 2018)
This study aims to determine the growth and production response of some mung bean varieties with the application of gibberellin at different concentrations in the saline field. This research was conducted at Hamparan Perak , District of Deli Serdang North Sumatera, Medan (± 3-9 m asl) from May - August 2017. The tretment was arranged by Randomized Block Design (RBD) with two factors, three mung green varieties (Vima-1, Vima-2, and Vima-3) and GA3 concentration (0 ppm, 100 ppm, 200 ppm). The results showed that there were significant diffrent among varieties on plant height, the number of pods per plant, and the diameter of the seed. Gibberellin concentration gives sinificant effect to the plant height in 3 and 5 week after pllanted, root volume, and seed diameter. The interaction between aplication gibberellins and varieties had a significant effect on the root volume.